UJI KANDUNGAN FENOLIK TOTAL DAN AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH ASAM PAYA (Eleiodoxa conferta (Griff.) Burret) TERHADAP Staphylococcus aureus. - Elisabeth SITORUS, Febrina Claudia; Dwi WULANSARI, Endang; SULISTYARINI, Indah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2020)
Asam paya (Eleiodoxa conferta (Griff.) Burret) contains phenolic compounds which can function as antibacterial agents against Staphylococcus aureus. Extraction using soxhlet with multilevel polarity, namely n-hexane and ethanol. The antibacterial activity test by TLC contact-bioautography showed that the phenolic compounds in the ethanol extract had antibacterial activity, and the diffusion test results showed that the ethanol extract had a larger inhibition zone diameter than the n-hexane extract. The total phenolic compound of extract was determined using the Folin-Ciocalteu reagent. The total phenolic compounds of Eleiodoxa conferta (Griff.) Burret. ethanolic extract is 7,326± 0,0989 mg GAE/gram sample. The ethanol extract was fractionated using a separating funnel, followed by purification with preparative TLC. The phenolic isolates obtained were tested for purity by three eluent TLC. The results of antibacterial activity diffution test and TLC contact-bioautography test showed that phenolic isolates had antibacterial activity against Staphylococcus aureus.